2017
DOI: 10.1016/j.ophtha.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Tele-education System to Enhance Retinopathy of Prematurity Training by International Ophthalmologists-in-Training in Mexico

Abstract: A tele-education system for ROP education was effective in improving the diagnostic accuracy of ROP by ophthalmologists-in-training in Mexico. This system has the potential to increase competency in ROP diagnosis and management for ophthalmologists-in-training from middle-income nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…19 Among children, educational programs can effectively increase the diagnostic accuracy of retinopathy of prematurity. 20 In the elderly Korean population, lifetime use of eye care was influenced by educational level. 21 A study in India also demonstrated that educational intervention may increase the use of eye care by targeting the rural population.…”
Section: Discussionmentioning
confidence: 99%
“…19 Among children, educational programs can effectively increase the diagnostic accuracy of retinopathy of prematurity. 20 In the elderly Korean population, lifetime use of eye care was influenced by educational level. 21 A study in India also demonstrated that educational intervention may increase the use of eye care by targeting the rural population.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a potentially reasonable model for universal newborn eye screening, it has been demonstrated that for ROP screening, diagnostic accuracy for ROP is affected by the experience of the image grader. [7][8][9][10][11] Therefore, it would be important to understand, in a well performed prospective study, the ability of physician and non-physician graders to accurately and reliably identify disease that requires referral in a universal newborn eye screening program. Indeed, three out of four pilot studies on universal newborn eye screening have been performed as expanded versions of ongoing ROP telemedicine programs.…”
Section: What Is the Significance Of Retinal Hemorrhages In Newborns?mentioning
confidence: 99%
“…This education system has been studied in two separate populations: 31 ophthalmology residents among 5 residency programs in the United States and 1 residency program in Canada and 58 ophthalmology residents and fellows from 1 program in Mexico. 53,54 Both studies found that the system was effective in improving diagnostic accuracy of ROP by ophthalmologists-in-training. Although this program has limitations, such as not tracking common errors made by trainees and not including examples of stage 4 or stage 5 ROP, the authors feel that improvements can be made and that this platform has potential to be used in a widespread manner to standardize evaluation of ROP images for both physician and nonphysician graders.…”
Section: Guidelines For Reading Centersmentioning
confidence: 99%